Analysis of the effectiveness of the combination of bevacizumab and irinotecan for the treatment of glial tumors (Research, Society and Development, 2022)
Glial tumors, or gliomas, are the most common type of brain tumor and have a high incidence, most of which are diffuse and prone to extensive infiltration into the brain parenchyma, causing tumor recurrence. High-grade gliomas, such as glioblastomas, are highly angiogenic and have high levels of proangiogenic factors, such as vascular endothelial growth factor (VEGF), essential for tumor neovascularization. The target to inhibit VEGF is bevacizumab, a humanized monoclonal antibody, with association with irinotecan, a topoisomerase I inhibitor. Thus, the objective of the following review is to analyze the effectiveness of the combination of bevacizumab and irinotecan for the treatment of glial tumors . This is a systematic literature review that used the PubMed, SciELO and Google Scholar platforms as a database for researching scientific articles, with a time frame between 2016 and 2021, in English. According to the search engine, 3 results were found after the exclusion criteria in PubMed and Google Scholar databases. Therefore, it was found that the combined chemotherapy of bevacizumab and irinotecan is effective in the treatment of glial tumors, moreover, the combination of both drugs has a higher overall survival rate than the isolated therapy of the antiangiogenic bevacizumab.